Measuring Visual Homogeneity and Congruence in Breast Cancer Awareness Campaigns - Germain Mesureur (Universitas Pendidikan Nasional, 2026)
Breast cancer awareness advertising is globally defined by the colour pink and the iconic pink ribbon. While this branding has elevated the cause, it has also sparked criticism regarding